Recent advances in the treatment of pathogenic infections using antibiotics and nano-drug delivery vehicles - Giau VV; An SSA; Hulme J (Dove Medical Press, 2019)
Vo Van Giau, Seong Soo A An, John Hulme Department of Bionano Technology, Gachon Bionano Research Institute, Gachon University, Seongnam-si, Gyeonggi-do, South Korea Abstract: The worldwide misuse of antibiotics and the subsequent rise of multidrug-resistant pathogenic bacteria have prompted a paradigm shift in the established view of antibiotic and bacterial–human relations. The clinical failures of conventional antibiotic therapies are associated with lengthy detection methods, poor penetration at infection sites, disruption of indigenous microflora and high potential for mutational resistance. One of the most promising strategies to improve the efficacy of antibiotics is to complex them with micro or nano delivery materials. Such materials/vehicles can shield antibiotics from enzyme deactivation, increasing the therapeutic effectiveness of the drug. Alternatively, drug-free nanomaterials that do not kill the pathogen but target virulent factors such as adhesins, toxins, or secretory systems can be used to minimize resistance and infection severity. The main objective of this review is to examine the potential of the aforementioned materials in the detection and treatment of antibiotic-resistant pathogenic organisms. Keywords: antibiotics, resistance, polymer, chitosan, gold, recombinant, targeted, pathogen